Potensi Senyawa Kimia Ekstrak Etanol Kelakai (Stenochlaena palustris) sebagai Antitrombotik - Saputri, Indah; Setiawati, Indah; Mukarramah, Mukarramah; An’nisa, Windy Sidratul; Afdella, Nor Afni; Komari, Noer (Herbal Medicine Journal, 2024)
Damage to blood vessels begins with the formation of platelet aggregation which then forms a thrombus in the artery, resulting in disruption of blood flow. Many efforts have been made to prevent platelet aggregation using herbal medicines. Kelakai is a typical Kalimantan plant thought to have antithrombotic potential. The aim of this research is to identify the potential of kelakai ethanol extract compounds as antithrombotics through in silico studies using virtual screening and molecular docking. The kelakai compound was obtained from GC-MS data taken from the ethanol extract of kelakai. The virtual screening results showed that the results of GC-MS analysis of ethanol extract found five compounds that had the potential to be antithrombotic. Molecular docking simulations with the antithrombin receptor protein (PDB ID: 1E04) show that the n-Hexadecanoic acid compound from kelakai ethanol extract has the lowest ∆G value of -8.72 kcal/mol. The n-Hexadecanoic acid compound from kelakai has potential as an antithrombotic.